2012
DOI: 10.1007/s10295-012-1142-9
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm establishment and heavy metal removal capacity of an indigenous mining algal-microbial consortium in a photo-rotating biological contactor

Abstract: An indigenous mining algal-microbial consortium was immobilised within a laboratory-scale photo-rotating biological contactor (PRBC) that was used to investigate the potential for heavy metal removal from acid mine drainage (AMD). The microbial consortium, dominated by Ulothrix sp., was collected from the AMD at the Sar Cheshmeh copper mine in Iran. This paper discusses the parameters required to establish an algal-microbial biofilm used for heavy metal removal, including nutrient requirements and rotational s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(31 citation statements)
references
References 45 publications
0
29
1
1
Order By: Relevance
“…This phenomenon has previously been reported by Das et al (2008), which found that due to metabolic processes the functional metal groups changed, as well as the competition of the metallic ions among themselves for adsorption sites. Gyure et al (1987) reported that low external pH reduced both surface binding and intracellular influx, which leads to the abundance of hydrogen ions which in turn compete with other cations for binding sites, resulting in poor metal bioaccumulation (Mehta and Gaur, 2005;Orandi and Lewis 2012). Trace metal uptake by macroalgae under acidic conditions in our study was substantially less than that observed at at neutral pH conditions (pH 7).…”
Section: Concentrations Of Metals Bioaccumulation By Various Algae Uncontrasting
confidence: 55%
See 1 more Smart Citation
“…This phenomenon has previously been reported by Das et al (2008), which found that due to metabolic processes the functional metal groups changed, as well as the competition of the metallic ions among themselves for adsorption sites. Gyure et al (1987) reported that low external pH reduced both surface binding and intracellular influx, which leads to the abundance of hydrogen ions which in turn compete with other cations for binding sites, resulting in poor metal bioaccumulation (Mehta and Gaur, 2005;Orandi and Lewis 2012). Trace metal uptake by macroalgae under acidic conditions in our study was substantially less than that observed at at neutral pH conditions (pH 7).…”
Section: Concentrations Of Metals Bioaccumulation By Various Algae Uncontrasting
confidence: 55%
“…Trace metal uptake by macroalgae under acidic conditions in our study was substantially less than that observed at at neutral pH conditions (pH 7). This may be ascribed to the fact that under acidic conditions release of trace metals by hydrogen ion occurred; while at a higher pH, trace metals have the tendency to render their chelation as observed in other studies (Warren and Haack, 2001;Orandi and Lewis, 2012).…”
Section: Concentrations Of Metals Bioaccumulation By Various Algae Unmentioning
confidence: 53%
“…Jia Yanping [9] study found that higher COD load not only increases the cost of adding carbon source, but also inhibit the autotrophic nitrification bacteria growth, and reduce the removal efficiency of NH4 + -N. When the inlet velocity is constant, the reflux ratio is determined by the circulation speed. And the change of the circulation rate has great influence on the dissolved oxygen in the wastewater and the thickness and shear stress of the liquid phase layer when the wastewater flows through the biological membrane, which further affects the operation efficiency of the reactor [10][11] . If continue to increase the return ratio, not only increased the thickness and the influence of mass transfer of liquid layer, the hydraulic shear stress increases greatly, resulting in the biofilm is large and scattered off, directly influence the operation efficiency, and high reflux ratio to consume more capacity, mechanical damage probability will increase [11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…The construction of the systems is more divers compared to the previous group as this concept allow bigger varieties (Fig.4) [61][62][63][64][65][66].…”
Section: Biofilm Based Photobioreactorsmentioning
confidence: 99%
“…The Algadisk photobioreactor design was based on a Rotating Biological Contractor (RBC) [64] and further modified in order to enhance and examine microalgae growth [62,66].…”
Section: Laboratory Scale Algadisk Photobioreactor Set-up and Operationmentioning
confidence: 99%